Psikoedukasi “Tumbuh Ceria” untuk Meningkatkan Perilaku Sosial Positif Anak Usia Dini - Pasenrigading, Andi Riola; Thohirah, Mursyidah Dianti; Siswanti, Dian Novita; Daud, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Psychoeducation is an effective approach to fostering positive social behavior in early childhood through developmentally appropriate learning strategies. This research aims to describe the implementation of the psychoeducational program ‘Tumbuh Ceria’ in enhancing empathy, cooperation, and social communication in children aged 4-6 years. The method used is a practice-based experimental program conducted at TK Agung Aras Telkomas. The program consists of three main sessions: recognizing emotions, sharing and cooperating, and appreciating differences. Observation results show that children experienced significant improvement in recognizing emotions, sharing abilities, and peacefully resolving conflicts. In conclusion, the psychoeducational approach through play media and storytelling is effective in developing children’s social skills. Teacher involvement also plays a key supporting factor in the success of this program.